EXAMINING MATHEMATICS DEPARTMENT STUDENTS' VIEWS ON THE USE OF MATHEMATICS IN DAILY LIFE - Hayal Yavuz Mumcu (Informascope, 2018)
Some researchers report that especially the students of the faculty of science and letters do not have sufficient knowledge of the practicability of mathematics since they are mostly interested in the pure aspect of mathematics, and they have difficulty in using their pure mathematical knowledge properly. So, this study aims to examine the views of mathematics students registered in the pedagogical formation program about the use of mathematics in daily life. To this end, an interview form with open-ended questions was administered to 86 pre-service mathematics teachers. The findings showed that pre-service teachers viewed mathematics as an indispensable part of life, but they treated real-life math and school math as separate types of math and had difficulty in relating them to each other. We recommend the use of real or real-like situations in the classroom environment in order to train individuals who can associate mathematics with everyday life and use it more effectively.